A descriptive study of Forcefully Displaced Myanmar Nationals (FDMN) presenting for care at public health sector hospitals in Bangladesh - Rashid, R; Uddin, AMS; Nu, PC; Salam, A; Barua, S; Mannan, A; Shahjahan, M; Ahmed, MU; Rahman, R; Dondorp, A; Maude, RJ; Deen, J; et al. (Francis and Taylor, 2020)
Background In 2017 hundreds of thousands of ‘Rohingya’ fled to camps for Forcefully Displaced Myanmar Nationals (FDMN) in Cox’s Bazar, Bangladesh. Objective To describe the FDMNs presenting for care at public health facilities in Bangladesh so as to understand the health problems faced by the FDMNs and the burden on these public health facilities. Methods This study combined a retrospective review of existing hospital and clinic data with prospective surveillance in government health care centres. Findings The retrospective data showed a 26% increase in the number of consultations at the Kutupalong community clinic, the primary health facility closest to the camps, from 19,567 in 2015 to 26,309 in 2019. There was a corresponding 11% increase in admissions to health facilities in the area, from 80,991 in 2017 to 91,424 in 2019. Prospective surveillance of 9,421 FDMNs seeking health care from July 2018 to December 2019 showed that 29% had an infectious disease, 20% nutritional problems, 12% pregnancy-related conditions and 7% trauma or injury. Conclusions Great uncertainty remains regarding the return of FDMN to their home country of Myanmar. The current on-going protests following the military coup adds further insecurity to the status of the Rohingya. The presence of a large migrant population relative to a smaller host community burdens the limited facilities and resources of the public health sector. Continued support by the international public health community and civil society organizations is needed.